Energy in Construction and Building Materials - Caggiano, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint collects works which stimulate and spread the latest knowledge on energy in construction and building materials, providing the basis for new ideas on various topics for young investigators as well as leading experts in the field of Materials Science and Engineering. The collection features fifteen research papers and one review study. The main research aim covers the topic of thermal energy storage in construction and building components.